(untitled) (Research, Society and Development, 2022)
Face of impacting changes in healthcare after COVID-19 pandemic, an imminent discussion is how to achieve humanization of care with so many safety barriers between healthcare providers and patients. The objective of this study is to propose an operational model to assist in the planning of actions and inspire work fronts in the fight against the Covid-19 pandemic, providing insights for future research and health policies. A search was carried out in PubMed Central using the terms “health care models” and “humanization of care”. Studies that presented conceptual and methodological aspects of health care models were selected, in addition to experience reports and systematic reviews. From the identification of critical elements for the humanization of care, an operational model was developed suggesting the most relevant themes that require solutions and organized actions to face the Covid-19 pandemic and its consequences. The proposed themes were transdisciplinary approach, health technology, cost-effectiveness, equity, social justice, education, health promotion, information access, safety and well-being, resources distribution, sustainability. This model may be useful to organize healthcare actions based on humanization of care, involving society in a collective effort to maintain the quality of care.